(untitled) (International Journal of Innovative Computing, 2018)
Cloud Computing have emerged into a very vast growing area which have a great impact towards the development other new technologies and application such as internet of things, sensors, artificial intelligence, social networks and business applications. With the new development of technology and applications, the production of data is increased and data have the property of being updated dynamically. That dynamic data is stored on cloud storages provided by third party service providers. The third party cloud storages cannot be solely trusted and the user does not have the control over the possession or integrity of data. The integrity is the major concern for that data as it is being intact not deleted, modified or destroyed intentionally or unintentionally. The researchers have presented several protocols such as Provable Data Possession (PDP) techniques which provide probabilistic approach for data integrity verification in which the verification is done on block level. To support dynamic nature of data the researchers have introduced different data structure along with PDP. Due to enormous amount of data and its dynamic nature, the integrity verification schemes causes high computational and communicational cost for metadata generation and node rebalancing of the data structures